1998
DOI: 10.1046/j.1365-2265.1998.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Leptin: in search of role(s) in human physiology and pathophysiology

Abstract: Obesity, a health problem reaching epidemic proportions in western countries, is an important risk factor for the most frequent diseases in the western world, i.e. diabetes, hypertension, cardiovascular diseases and certain types of cancer. Thus, significant research efforts have been focusing on its aetiology, prevention and treatment. The recent discovery of leptin (from the Greek word leptos: i.e. thin), the product of the ob gene (Zhang et al., 1994), has greatly advanced our understanding of body adiposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
118
0
10

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(132 citation statements)
references
References 232 publications
(283 reference statements)
4
118
0
10
Order By: Relevance
“…Leptin, initially discovered as a regulator of food intake and energy expenditure, is emerging as a pleiotropic molecule involved in a variety of physiological and pathological functions (43). Alterations in leptin levels and͞or in the responsiveness to leptin have been reported not only during starvation and obesity, but also in patients affected by diabetes, renal failure, hypothyroidism, and AIDS (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptin, initially discovered as a regulator of food intake and energy expenditure, is emerging as a pleiotropic molecule involved in a variety of physiological and pathological functions (43). Alterations in leptin levels and͞or in the responsiveness to leptin have been reported not only during starvation and obesity, but also in patients affected by diabetes, renal failure, hypothyroidism, and AIDS (43).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in leptin levels and͞or in the responsiveness to leptin have been reported not only during starvation and obesity, but also in patients affected by diabetes, renal failure, hypothyroidism, and AIDS (43). T lymphocytes and cytokines are critical mediators of hepatic inflammation in patients affected by viral, allergic, autoimmune, and possibly alcoholic liver disease (44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Leptin regulates TRH expression (28). Recent evidence has suggested that the relationship between leptin levels and FM is curvilinear, so that leptin secretion increases exponentially with increasing FM (29). Insulin also increases total leptin levels (30).…”
Section: Thyroid Nodulementioning
confidence: 99%
“…Os trabalhos iniciais sobre leptina versavam sobre seus efeitos biológicos mais evidentes: diminuição do peso e da ingestão alimentar (2). Posteriormente, descobriu-se que a leptina atuava em sistemas fisiológicos independentes do controle de energia (3). Recentemente, ensaios clínicos com leptina recombinante fecharam um ciclo de investigações que começaram com modelos animais de obesidade e chegaram até o tratamento da obesidade em humanos (4,5).…”
unclassified